EFEKTIFITAS METODE KANGGURU MENGURANGI RASA NYERI PENYUNTIKAN INTRAMUSCULAR PADA BAYI BARU LAHIR DI PMB SITI FATIMAH, AMD. KEB TAHUN 2023 - Purwati, Siti Nia; Gapmelezy, Ezzy (Jurnal Ilmiah Global Education, 2023)
Prevention of pain in newborns is by nonpharmacological mens effective to reduce pain in intramuscular injection of newborn. The use of kangarro method is a nonpharmacological method that can reduce intramuscular injection pain physiologically. Based on the above, researchers are interested in conducting a study entitled “Effectiveness of Kangoroo Methods to Reduce Pain in Intramuscular Injection in Newborns in PMB Siti Fatimah”.Knowing the effectiveness of kangaroo methods reduces pain in intramuscular injections in newborns in PMB Siti Fatimah, Kel Kuta Jaya Kec Pasar Kemis, Kab Tangerang.The design of this study uses quasi-experimental. With the posttest only, control group approach. Population of newborns with inclusion criteria Normal newborns weighing 2500 – 4000 grams, in stable condition not in a state of asphyxia, apnea or shock, babies without physical disabilities, born at PMB Siti Fatimah. Sampling was taken by purposive sampling with a sample of 60 respondents, 30 control groups and 30 intervention groups. This research was conducted at PMB Siti Fatimah in May-June 2023. Measurements used observation with the NIPS (Neonatal Infant Pain Scale) measurement tool. Data analysis using univariate analysis, namely the mean, median, minimum, maximum and standard deviation and bivariate analysis using the independent T-test program SPSS 25. The average intramuscular injection pain scale in the control group was 4.97, the median was 5, the minimum value was 3 and the maximum was 7 with a standard deviation of 1.65, while the average intramuscular injection pain scale in the intervention group with the kangaroo method was 2.70, the median was 3, the value minimum 2 and highest 4 with a standard deviation of 0.70. Statistical test results There is an effect of the kangaroo method on reducing pain in intramuscular injections in newborns at PMB Siti Fatimah, Amd.Keb. with a p-value of 0.000 < ɑ (0.05). There is a significant effect of the kangaroo method on reducing intramuscular injection pain in newborns. It is hoped that this method can be implemented in the care of newborns, especially to reduce the pain of injecting Hb0 and Vit K given intramuscularly.